Case Report: Grade 2 Metastatic Pancreatic Neuroendocrine Tumor With Progression of One Metastasis After Pregnancy to Grade 3 Large-Cell Neuroendocrine Carcinoma: One Case Cured by Resection With Genomic Characterization of the Two Components - Raoul, Jean-Luc; Heymann, Marie-Françoise; Dumont, Frédéric; Morel, Alain; Senellart, Hélène; Bertucci, François (Frontiers in Oncology, 2021)
Temporal and spatial tumor heterogeneity can be observed in pancreatic neuroendocrine tumor. We report the case of a young woman with long term stabilization of a G2 metastatic pancreatic NET that, after pregnancy, suddenly progressed into one single liver metastasis corresponding to a transformation into G3 large-cell neuroendocrine cancer. The patient underwent liver resection (the progressive and one dormant metastasis). With a 45 months follow-up the patient is without evolutive disease. Exome sequencing of the two metastases revealed completely different genomic signatures and gene alterations: the dormant metastasis was MSS without any gene alteration; the poorly differentiated tumor was MSI, with gain of many mutations including MEN1, BCL2, MLH1 and TP53 corresponding to a mutational signature 11. Could temozolomide play a role in this transformation?